A review of West African monsoon penetration during Green Sahara periods; implications for human evolution and dispersals over the last three million years. Issue 1 (22nd October 2021) - Larrasoaña, Juan Cruz
Abstract: Green Sahara periods (GSPs) represent episodes during which the present-day Sahara was transformed into a savannah in response to intensification of the West African monsoon (WAM). Although GSPs might have dramatically altered the size, structure, and connectivity of human populations in Africa and nearby regions of Asia, their significance for human evolution remains unknown due to the problems involved in gauging the penetration of the WAM over the Sahara at evolutionary timescales. Here I reanalyse monsoon run-off and dust records back to 3 million years ago from Eastern Mediterranean ODP Site 967, and assimilate them with North African palaeoenvironmental data to substantiate penetration of the WAM front during GSPs to latitudes beyond 28°N. These results, coupled with demographic and ecological data for modern hunter-gatherers, point to a significant expansion of human populations during GSPs compared with background desert conditions. Given the clustering of GSPs around long-term maxima in the eccentricity of the Earth's orbit, I propose that recurrent periods of human population expansion driven by GSPs led to an increased number of favourable mutations. Along with environmental factors favourable for triggering epigenetic changes, this might have led to the rise in enhanced phenotypic plasticity that underpins the speciation of hominin lineages at times of high climate variability envisaged by the variability selection hypothesis. Clustering of GSPs around the Pliocene/Pleistocene boundary, simultaneously with a protracted period of wetter conditions in East Africa and the Sinai Peninsula, further suggests that the initial colonization of Eurasia by hominins occurred circa 2.6 Ma, much earlier than typically considered.